Design of a two-Degree-of-Freedom Controller for a Magnetic Levitation System Based on LQG Technique - Ibraheem, Ibraheem Kasim (Nahrain University College of Engineering Journal, 2017)
A new control design procedure has been proposed in this paper based on the LQG control design. A two degree of freedom controller with integral action is obtained and tested on the magnetic levitation system, which is a good test-bed for control design because of its nonlinearity and unstability with practical uses in high-speed transportation and magnetic bearings. Simulations are performed under MATLAB environment and included to highlight that the proposed controller accurately achieves position tracking for different kinds of reference inputs